Outcome of Surgical versus Non-Surgical Treatment for Proximal Humerus Fractures; a Cross-sectional Study - Saeed Kokly; Ramin Etemadi; Omid Momen; Seyyed-Mohsen Hosseininejad; Sina Shakiba (Journal of Orthopedic and Spine Trauma)
Objectives: Proximal humerus fracture (PHF) is one of the most common upper limb fractures. PHF is more common among the elderly and usually occurrs after a fall. high-energy trauma causes this form of fracture in young persons. There are several treatment options for PFH, including surgical and non-surgical precedures. We aimed to compare the results of surgical and non-surgical treatment outcomes in Iranian patients with PHF.